Crime is not the problem : lethal violence in America - Zimring, Franklin E. (Studies in crime and public policy., 1997)
This text has three main aims: the first is to show that what separates the USA from other countries is not crime rates but lethal violence. Crimes like burglary and theft are a part of modern urban life worldwide; shootings and stabbings are not - they are particularly American. Why is this so? Secondly, the book seeks to clarify the causes of violence by looking at the proximate causes of deadly violence - guns, violence in the media, drugs and the tradition of lethal violence are all examined. The concluding section of the book concerns the prevention of lethal violence as a priority issue. The authors discuss a range of anti-violence alternatives from change in the criminal law to social and physical environmental factors and social values and attitudes.